1943
DOI: 10.1021/ie50399a005
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidations of Naphthalene Series

Abstract: Vapor-phase catalytic oxidations were made on commercial naphthalene, practical Tetra-Iin, 95 per cent 2-methylnaphthalene and 70 per cent 1 -methylnaphthalene to yield chiefly phthalic anhydride. Quinone by-products were found in small amounts. The most successful catalyst consists of pure pyrolytic vanadium pentoxide fused on glassy silica gel. A tin-bearing vanadium catalyst was tried with but moderate success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1948
1948
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Vanadium-based catalysts were widely used in catalytic oxidation reactions because of its excellent catalytic performance. Shreve et al studied catalytic oxidation of 1-methyl naphthalene and 2-methyl naphthalene to phthalic acid with V 2 O 5 as the catalyst. Using vanadate catalyst, xylene could be oxidized to toluic aldehyde and phthalic anhydride .…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium-based catalysts were widely used in catalytic oxidation reactions because of its excellent catalytic performance. Shreve et al studied catalytic oxidation of 1-methyl naphthalene and 2-methyl naphthalene to phthalic acid with V 2 O 5 as the catalyst. Using vanadate catalyst, xylene could be oxidized to toluic aldehyde and phthalic anhydride .…”
Section: Introductionmentioning
confidence: 99%
“…Elution chromatography of a 1.00-gram sample of the reaction product mixture from run No. 7 over chromatographic alumina with eluting solvent mixture ranging from petroleum ether through carbon tetrachloride, chloroform, and finally acetone yielded 23 fractions which were evaporated to dryness in tared flasks. A total of up to 12.3 wt.% pure naphthalene was detected in the product.…”
Section: Resultsmentioning
confidence: 99%
“…He concluded that naphthalene is not a reaction intermediate in the oxidation of methylnaphthalenes to phthalic anhydride. In the research related below, naphthalene was conclusively detected under reaction conditions which are well known to effect its further oxidation to phthalic anhydride (2,4,72,76,79,23). Naphthalene was first detected and isolated in the recovered hydrocarbon mixture obtained from the fluid-bed oxidation of 2,3-dimethylnaphthalene to phthalic anhydride.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…REACTION KINETICS Performance data on vapor phase catalytic oxidations are reported by McBee, Hass, and Wiseman (148) of ethylene using silver oxide as a catalyst over the temperature range from 225°t o 325°C ., of fatty oils by Faith and Rollins (68), of ethyl alcohol by Michels and Keyes (158), and of ammonia to nitrous oxide using manganese oxide-bismuth oxide as the catalyst by Kobe and Hossman (121). Using a catalyst of vanadium oxide on silica gel, Shreve and Welborn investigated the vapor phase oxidation of naphthalene, Tetralin, 2-methylnaphthalene, and 1-methylnaphthalene with air (211). Kinetic data have been given on the vapor phase oxidation of halogenated hydrocarbons to maleic and fumaric acid, including -butyl chloride, -butyl bromide, n-dichlorobutane, mixed amyl chlorides, dichloropentane, polychloropentanes, and -hexyl chloride, with determination of the effects of temperature, space velocity, feed composition, and catalyst (65).…”
Section: Industrial and Engineering Chemistrymentioning
confidence: 99%